2014
DOI: 10.1097/jto.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy in Patients with Previous Pneumonectomy: Safety and Efficacy

Abstract: SBRT in patients with prior pneumonectomy poses challenges because of limited lung reserve. However, local control and long-term survival can be achieved using SBRT in this inoperable population. Careful consideration must be given to radiation planning to minimize the risk of radiation pneumonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 23 publications
3
31
0
1
Order By: Relevance
“…Haasbeek and colleagues analyzed 15 patients status-post pneumonectomy who subsequently underwent SBRT for a new stage 1 NSCLC, identifying grade ≥3 pneumonitis in 2 of 15 patients (13.3%) [18]. Similarly, Thompson and colleagues report outcomes for a cohort of 13 patients with prior pneumonectomy subsequently treated with SBRT, identifying 2 cases of grade 3+ pneumonitis (15.4%) [17]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Haasbeek and colleagues analyzed 15 patients status-post pneumonectomy who subsequently underwent SBRT for a new stage 1 NSCLC, identifying grade ≥3 pneumonitis in 2 of 15 patients (13.3%) [18]. Similarly, Thompson and colleagues report outcomes for a cohort of 13 patients with prior pneumonectomy subsequently treated with SBRT, identifying 2 cases of grade 3+ pneumonitis (15.4%) [17]. …”
Section: Discussionmentioning
confidence: 99%
“…A total of 2 small case series (references 17 -18) address the risk of SBRT in post-pneumonectomy patients, and none specifically evaluate potential risks in lobectomy patients. We present an analysis of 84 consecutively treated patients with T1-T2b NSCLC treated with 88 courses of SBRT for 94 lung tumors, including 17 patients with prior lung resection.…”
Section: Clinical Practice Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐small cell lung cancer (NSCLC) is the leading cause of death from cancer worldwide . With the development of radiotherapy, stereotactic ablative radiotherapy (SABR) has become an effective treatment for NSCLC . RTOG 0236 suggested that peripheral stage I non‐small cell tumors treated with SABR could achieve acceptable local control (LC) and overall survival (OS) .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 With the development of radiotherapy, stereotactic ablative radiotherapy (SABR) has become an effective treatment for NSCLC. [3][4][5][6] RTOG 0236 suggested that peripheral stage I non-small cell tumors treated with SABR could achieve acceptable local control (LC) and overall survival (OS). 7 A phase 3 randomized trial comparing SABR with surgery has suggested that SABR was better tolerated and might lead to better OS compared with surgery for operable clinical stage I NSCLC.…”
Section: Introductionmentioning
confidence: 99%